Key Performance Indicator Application In Performance Assessment Of The Best Employees With Simple Additive Weighting Methods On General And Hr Division Case Study: Perum Percetakan Negara RI - Meilina, Popy; Risanty, Rita Dewi; Nurwahyudin, Eka (Universitas Mercu Buana, 2018)
Management of human resources (HR) of a company greatly influences many aspects in determining the success of the company's work. One of the most important in the management of human resources (HR) in a company is the selection of the best employees periodically to encourage employee morale in increasing their dedication and performance. But in reality the PNRI Public Corporation is still not optimal in conducting the best employee selection, this is due to the unavailability of media that can process employee appraisals and provide recommendations in the selection of the best employees. This study aims to determine the best employee assessment and selection procedures at PNRI Public Corporation and to produce the best employee decision support system based on the needs of the PNRI Public Corporation. In determining the best employees in Perum PNRI, the system uses the Simple Additive Weighting (SAW) method. The criteria that have been used in the PNRI Public Office are attendance, work motivation, communication and collaboration, understanding and mastery of work, self-development, achievement of national work targets, rewards and sanctions. This system was developed with the PHP and MySQL programming languages. This information system can be used to process employee data from the incoming employee process, the employee appraisal process, the best employee selection process, to the process of creating employee value reports. The output in this system is the value of the best employee selection calculation with the SAW method and the best employee recommendations for PNRI Public Corporation and the assessment statistics display every quarter.